2023
DOI: 10.7717/peerj.15405
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of cognitive impairment in patients undergoing ileostomy for colorectal cancer: a retrospective analysis

Abstract: Background Early detection of cognitive impairment in patients undergoing ileostomy for colorectal cancer may help improve patient outcomes and quality of life. Identifying risk factors and clinically accessible factors is crucial for prevention and treatment. Objective This retrospective study aimed to identify risk factors for post-operative cognitive impairment in patients undergoing ileostomy for colorectal cancer and to explore potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…In another retrospective study, preoperative low physical activity was suggested in patients with gastrointestinal cancer as a predictor of POD, independent of confounding factors [ 11 ]. Similarly, preoperative low skeletal muscle mass (LSMM) [ 12 ] and exercise intensity [ 13 ] are associated with POD in older adult patients undergoing colorectal cancer (CRC) surgery. Patients with LSMM can be identified based on gender and skeletal muscle index (SMI) by assessing the cross-sectional area of skeletal muscle at the third lumbar vertebra (L3) level on computed tomography (CT) [ 14 ].…”
Section: Exercise Decrease the Risk And Severity Of Podmentioning
confidence: 99%
See 1 more Smart Citation
“…In another retrospective study, preoperative low physical activity was suggested in patients with gastrointestinal cancer as a predictor of POD, independent of confounding factors [ 11 ]. Similarly, preoperative low skeletal muscle mass (LSMM) [ 12 ] and exercise intensity [ 13 ] are associated with POD in older adult patients undergoing colorectal cancer (CRC) surgery. Patients with LSMM can be identified based on gender and skeletal muscle index (SMI) by assessing the cross-sectional area of skeletal muscle at the third lumbar vertebra (L3) level on computed tomography (CT) [ 14 ].…”
Section: Exercise Decrease the Risk And Severity Of Podmentioning
confidence: 99%
“… Mosk et al [ 12 ] 251 patients 76 (IQR, 73–80) Retrospective observational cohort study SMI Colorectal cancer surgery DOSS POD occurred significantly more in patients with LSMM (25%) compared with patients without LSMM (10%), p = 0.006. Xu et al [ 13 ] 122 patients 72.77 ± 5.38 Retrospective study Exercise intensity Ileostomy for colorectal cancer MoCA and FACT-Cog Exercise intensity is independent predictors of postoperative cognitive impairment. Makiguchi et al [ 16 ] 122 patients 60.3 (± 11.2) Nonrandomized, retrospective cohort study SMI Free flap repair after oral cancer resection DSM-IV Lower SMI was identified as significant independent risk factors for POD (OR 2.52; p = 0.035).…”
Section: Exercise Decrease the Risk And Severity Of Podmentioning
confidence: 99%
“…Predictive models have the potential to support physicians in implementing precision medicine, thus enabling the development of individualized and effective treatment strategies [6][7][8][9]. The objective of this investigation was to examine the present status and potential risk factors linked to POD in elderly individuals undergoing radical prostatectomy, as there has been little focus on them.…”
Section: Introductionmentioning
confidence: 99%